Arturo Ruiz del Pozo, Selvynas (1978): Brief annotations - Ocampo Grey, Álvaro Antonio (2024)
The sophistication of sound experimentation by Peruvian composers has a long history. Composers of the generation of the 50s such as César Bolaños and Edgar Valcárcel were immersed in the timbral search that had developed with concrete music and electronic music in the European musical avant-garde of the 40s and 50s, respectively. As a student of that school, the composer Arturo Ruiz del Pozo established himself as a prominent exponent of electroacoustic music, but seeking a special timbral manifestation of Peruvian identity, difficult to wield within the framework of a language, at the time, so far removed from the classical, popular and traditional instrumental musical trends of the nation.